Systematic Literature Review : Potential of Kirinyuh Leaves ( Chromolaena Odorata ) As A Wound Treatment - Azka Fariz Hidayat; Miftahul Khaira; Dira Sabrina Putri; Diva Rayana; Cut Nadzifa Thahira; Fathia Maulina; Nazwa Ardila; Diana Setya Ningsih (PT Inovasi Pratama Internasional, 2026)
A wound is damage to body tissue that can occur due to cuts, impacts, heat, infection, or chemicals. Wounds that are not properly treated can cause infection, inflammation, bleeding, and disruption of new tissue formation. One plant that has been widely studied is the kirinyuh leaf (Chromolaena odorata). This study used the Systematic Literature Review (SLR) method. Articles were searched through Google Scholar, PubMed, ScienceDirect, Semantic Scholar, Garuda, and Crossref for the period 2017-2025. The article selection process used the PRISMA flow through the stages of identification, screening, eligibility, and inclusion. The initial search results obtained 186 articles. After removing duplicate articles, screening titles and abstracts, and full-text examination, 41 final articles were obtained that met the analysis requirements. The articles analyzed consisted of laboratory experimental studies, in vivo, in vitro, literature reviews, systematic reviews, phytochemical analysis, and GC-MS or UPLC-MS analysis. The results showed that flavonoids were the compounds most frequently found in kirinyuh leaves and were most associated with accelerated wound healing. Kirinyuh leaves have been shown to accelerate wound closure, increase collagen formation, increase angiogenesis, repair fibroblasts, and inhibit the growth of bacteria such as Staphylococcus aureus, Escherichia coli, Salmonella typhi, MRSA, and ESBL. Burn wound research shows that N-hexane extract of kirinyuh leaves at a concentration of 30% provides a healing rate of 79% on the 21st day. Another study showed that a serum combination of kirinyuh essential oil and curcumin provides healing of diabetic wounds by 68.068%. The most commonly used dosage forms are gels, ointments, creams, serums, sprays, essential oils, and topical extracts.